INTERSTELLAR ABSORPTION IN SOME DIRECTIONS - Yasinskaya, M. P.; Dragunova, A. V. (Одеські астрономічні публікації, 2017)
Interstellar absorption has been investigated towards Captain Areas KA-64, KA-65, KA-86, KA-87, KA- 88, KA-98 by the method of a colour excess. The star magnitudes V and colour indexes (B-V) of stars were received by Yasinskaya et al. (Odessa Astron. Publ., 2000, v.13, p.4). The stars of all spectral classes had been used for determination of quantity of interstellar absorption. The received curves of absorption have allowed to estimate the density of an absorption substance in explored directions. The results are presented in a graphical view. The random error of determination of complete visual absorption for KA-64, KA-86, KA-88 is ±0m.10, for KA-65 is equal to ±0m.09, for KA-87, KA-98 - ±0m.11. The random error of determination of distance for all areas is 110 pc on the first kiloparsec. At the distance of 2 kpc the random error increases up to 220 pc.